MicroRNAs: emerging players in apical periodontitis - Zhen SHEN; Renato Menezes SILVA (University of São Paulo, 2021)
Abstract Apical periodontitis is an inflammatory disorder of periradicular tissues developed from endodontic infections. Understanding its pathophysiology and the underlying molecular mechanisms is key to the advancement of endodontics. MicroRNAs (miRNAs), a group of evolutionarily conserved small non-coding RNAs, may be phenotypically and functionally associated with the pathogenesis of apical periodontitis. Several studies have focused on the role of miRNAs in the pulp and periradicular biology, and they have demonstrated their essential functions, such as initiating odontogenic differentiation and promoting pro- or anti-inflammatory responses in pulpitis. Up to date, over 2,000 miRNAs have been discovered in humans; however, only few have been reported to associate with apical periodontitis. Therefore, identifying miRNAs involved in diseased apical tissues and conducting functional studies are important in expanding our current knowledge of pulp and periradicular biology and exploring novel therapeutic avenues. In this review, we revisit current models of apical periodontitis and miRNA biogenesis, analyze existing evidence of the involvement of miRNAs in diseased apical tissues, and discuss their diverse functions and potential values. Based on their sheer abundance, prolonged stability in biofluid, and relative ease of sampling, miRNAs may be a useful tool to be developed as diagnostic biomarkers for apical periodontitis. Furthermore, it can be used as therapeutic targets in conjunction with conventional endodontic therapies.